Relationship between monocyte/lymphocyte ratio and non-culprit plaque vulnerability in patients with acute coronary syndrome: An optical coherence tomography study - Zhang, Ting-yu (Medicine (Baltimore), 2020)
The importance of monocyte/lymphocyte ratio (MLR) has been indicated in the initiation and progression of coronary artery disease. However, few previous researches demonstrated the relationship between MLR and plaque vulnerability. We aimed to investigate coronary non-culprit plaque vulnerability in patients with acute coronary syndrome (ACS) by optical coherence tomography (OCT). A total of 72 ACS patients who underwent coronary angiography and OCT test in Beijing Anzhen Hospital were included in this retrospective study. The plaque vulnerability and plaque morphology were assessed by OCT. The non-culprit plaque in high MLR group exhibited more vulnerable features, characterizing as thinner thickness of fibrous cap (P = .013), greater maximum lipid core angle (P = .010) and longer lipid plaque length (P = .041). A prominently negative liner relation was found between MLR and thickness of fibrous cap (R = –0.225, P = .005). Meanwhile, the proportion of OCT-detected thin cap fibro-atheroma (TCFA) (P = .014) and plaque rupture (P = .017) were higher in high MLR group. Most importantly, multivariable logistic regression analysis showed MLR level was identified as an independent contributor to the presence of TCFA (OR:3.316, 95%: 1.448–7.593, P = .005). MLR could differentiate TCFA with a sensitivity of 60.0% and a specificity of 85.1%. Circulating MLR level has potential value in identifying the presence of vulnerable plaque in patients with ACS. MLR, as a non- invasive biomarker of inflammation, may be valuable in revealing plaque vulnerability.